Implementation of Sustainable Growth Rate in Indonesia’s Stock Market - Valentino Budhidharma (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
The Indonesia financial market is facing a recession in 2020. The decline in the financial market has been started since 2018. The pandemic of Covid-19 worsens the condition. This paper examines the SGR, AGR, and DPR of five selective random sampling banks from the financial sector in the Indonesian capital market to find out what is happening. The findings show that even though the SGR value is decreasing, most banks show an increasing value of DPR. One possible cause is banks do not have other places for investments so that they give the profit to shareholders.